Analysis of Tour Guide Service Quality on Tourist Satisfaction: Case Study PT. Bali Prima Holidays - Gunawan, I Made Krishna Wira; Zuraida, Lukia; Darmiati, Made (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This research aims to determine the influence of tour guide service quality on tourist satisfaction at PT. Bali Prima Holidays. The method of research used is quantitative, using data-gathering techniques through questionnaires. The research sample amounted to 100 respondents who were tourists who had used the tour guide services of PT Bali Prima Holidays. The data analysis technique uses simple linear regression analysis. The results showed that service quality positively and significantly influences tourist satisfaction, with a t value of 12.091 > t table 1.660 and a significance value of 0.000 < 0.05. Service quality can have an influence of 59.5% on tourist satisfaction. Respondents' overall service quality assessment is in a suitable category with an average value of 3.98. The aspect rated best is the appearance of a neat, attractive, and professional tour guide. In contrast, the element that needs to be improved is the ability of tour guides to communicate well and provide information precisely and clearly. This research implies that PT Bali Prima Holidays must maintain and enhance the quality of tour guide services, especially on aspects rated well by tourists, to maintain tourist satisfaction. In addition, further research needs to be done to identify other factors that also affect tourist satisfaction.